Analisis Efektivitas Pengelolaan Risiko Bencana Melalui Pendekatan Good Governance Di Badan Penanggulangan Bencana Daerah Kabupaten Nias Selatan Tahun 2025 - Kiki Asrifa Dinen (Hikamatzu | Journal of Multidisciplinary, 2025)
Nias Selatan Regency is one of the disaster-prone areas in North Sumatra Province, facing recurring threats such as floods, landslides, and high waves. These conditions demand an effective and sustainable disaster risk management system based on the principles of good governance. This study was conducted in the working area of the Regional Disaster Management Agency (BPBD) of Nias Selatan Regency and aims to analyze the level of effectiveness in disaster risk management and evaluate the application of good governance principles, including transparency, accountability, participation, effectiveness and efficiency, and responsiveness. The research employed a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation. The study involved seven informants, consisting of BPBD structural officials, sub-district heads, village heads, and affected community members. The results indicate that disaster risk management by BPBD has not been fully optimal. The implemented programs are not yet evenly distributed, lack sustainability, and use no standardized indicators of success, while public involvement remains limited. The application of good governance principles is also not fully realized, especially in terms of information transparency and public reporting. This research recommends strengthening institutional capacity, utilizing digital information systems, and enhancing coordination and community participation in all stages of disaster risk management